Panitumumab following disease progression on cetuximab in patients with metastatic colorectal cancer: A retrospective review. (April 2014) - Lau, S Cecilia; Chung, Vincent; Lim, Dean; Shibata, Stephen
Despite advances in treatment options for metastatic colorectal cancer over the past decade, the number of chemotherapy agents available remains limited. We report here a retrospective review of 11 patients who were treated with panitumumab following documented disease progression on cetuximab. Two patients demonstrated minor radiographic responses, albeit only for a short period of time. We conclude that the use of one epidermal growth factor receptor inhibitor following failure on the other may be of benefit to patients who would otherwise have no other treatment options. However, studies to help identify the subset of patients who might benefit from this strategy are needed.